1976
DOI: 10.1159/000178716
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Production by Ovarian Follicles of the Domestic Cat <i>(Felis catus)</i>

Abstract: In order to determine whether the ovarian follicles of the domestic cat which normally ovulates following copulation, were similar to those of the rabbit steroidogenically, the following experiments were carried out. Follicles were dissected out of ovaries from nine estrous cats throughout the year and incubated in medium alone or with luteinizing hormone (LH) or human chorionic gonadotropin (HCG). Media were removed every 15 min and stored frozen until analyzed for testosterone using established radioimmunoas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…However, plasma concentrations of MBG were recently found to be significantly higher (p < 0.05) in intact females compared to spayed females (Rutherfurd et al, 2002). Taken together, these studies, and in particular, the last study indicate that estradiol may have an effect on urinary felinine concentrations or the differences between spayed and intact females could be due to the testosterone produced in the ovary (YoungLai et al, 1976).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, plasma concentrations of MBG were recently found to be significantly higher (p < 0.05) in intact females compared to spayed females (Rutherfurd et al, 2002). Taken together, these studies, and in particular, the last study indicate that estradiol may have an effect on urinary felinine concentrations or the differences between spayed and intact females could be due to the testosterone produced in the ovary (YoungLai et al, 1976).…”
Section: Introductionmentioning
confidence: 64%
“…Previous results showed that spayed female cats have significantly lower concentrations of plasma MBG (Rutherfurd et al., 2002) and urinary felinine (Hendriks et al., 1995b) than their intact counterparts. The ovaries in cats have been found to produce small amounts of testosterone (YoungLai et al 1976), and it is possible that the significant reduction in plasma MBG found by Rutherfurd et al. (2002) is due to a reduction in testosterone concentrations in the blood, as a result of the absence of ovaries.…”
Section: Discussionmentioning
confidence: 99%